MBOAT7 rs641738 increases risk of liver inflammation and transition to fibrosis in chronic hepatitis C - Khaled Thabet (Nature Communications, 2016)
Chronic Hepatitis C infection is associated with a broad spectrum of liver pathologies, ranging from inflammation to fibrosis and liver cancer. Here Thabet et al. identified a polymorphism in the gene MBOAT7 that is associated with increased hepatic inflammation and higher risk of fibrosis development and progression.